PENDIDIKAN PONDOK PESANTREN TRADISONAL DALAM PERSEPKTIF PENDIDIKAN ISLAM INDONESIA - Ahmad Syihabudin (STAI Darul Qalam Tangerang, 2025)
Whether it is recognized or not, Pesantren is the oldest educational institution that has been inherent in the course of Indonesian life since hundreds of years ago and has made many significant contributions to the development of this nation, so it is not surprising that education experts like Ki Hajar Dewantoro and Dr. Soetomo once dreamed of a model of the pesantren education system as a model of national education. For them, the pesantren education model is a smart creation of Indonesian culture that has character and should be maintained and developed. Because there are many